2017
DOI: 10.1152/ajplung.00173.2017
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness induces remodeling phenotypes in pulmonary artery smooth muscle cells via YAP/TAZ-mediated repression of cyclooxygenase-2

Abstract: Pulmonary arterial stiffness is an independent risk factor for mortality in pulmonary hypertension (PH) and plays a critical role in PH pathophysiology. Our laboratory has recently demonstrated arterial stiffening early in experimental PH, along with evidence for a mechanobiological feedback loop by which arterial stiffening promotes further cellular remodeling behaviors (Liu F, Haeger CM, Dieffenbach PB, Sicard D, Chrobak I, Coronata AM, Suárez Velandia MM, Vitali S, Colas RA, Norris PC, Marinković A, Liu X, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 87 publications
1
59
0
Order By: Relevance
“…Here, we observed that coating with type IV collagen had a stronger effect on YAP nuclear translocation in donor PAECs than in IPAH, as the latter, under basal conditions, already had increased YAP nuclear signal. Importantly in IPAH, increased YAP activation has been reported for other vascular cells, such as smooth muscle cells (5,43,44). Here, we show first evidence for a similar phenotype in PAECs.…”
Section: Discussionsupporting
confidence: 80%
“…Here, we observed that coating with type IV collagen had a stronger effect on YAP nuclear translocation in donor PAECs than in IPAH, as the latter, under basal conditions, already had increased YAP nuclear signal. Importantly in IPAH, increased YAP activation has been reported for other vascular cells, such as smooth muscle cells (5,43,44). Here, we show first evidence for a similar phenotype in PAECs.…”
Section: Discussionsupporting
confidence: 80%
“…The relationship between COX-2 and vascular remodeling was described in the pulmonary circulation. Pulmonary arterial stiffness occurs early in experimental pulmonary hypertension and is an independent risk factor for mortality in pulmonary hypertension ( 154 ). COX-2 is upregulated in pulmonary artery smooth muscle cells during hypoxia, associated with upregulation of the endothelin receptor ( 155 ) and intravascular macrophage accumulation ( 156 ).…”
Section: Cyclooxygenase-2 (Cox-2) Prostaglandin Signaling and Artermentioning
confidence: 99%
“…COX-2 is upregulated in pulmonary artery smooth muscle cells during hypoxia, associated with upregulation of the endothelin receptor ( 155 ) and intravascular macrophage accumulation ( 156 ). The transcriptional regulator Yes-associated protein activity is increased in pulmonary hypertension in pulmonary artery smooth muscle cells and is necessary for development of stiffness-dependent remodeling phenotypes ( 154 ). However, selective COX-2 inhibition impairs the balance of vascular mediators, enables vascular hyperplasia, remodeling of the systemic vessels, platelet deposition, intravascular thrombosis, and is associated with several cardiovascular events ( 155 ).…”
Section: Cyclooxygenase-2 (Cox-2) Prostaglandin Signaling and Artermentioning
confidence: 99%
“…Furthermore, in pulmonary vascular cells exposed to increasing extracellular matrix stiffness, a recently identified PH trigger (41), mechanoactivation of Yes-associated protein 1 (YAP) and the transcriptional coactivator with a PDZ-binding motif (TAZ, also known as WWTR1), induced the reductive enzyme glutaminase 1 (GLS1), thus promoting glutaminolysis and hyperproliferation (40). Glutaminolytic reprogramming was increased in the vascular lesions of PAH patients and animal models, and multiple vascular cell types in PH relied on the YAP/TAZ-GLS1 axis (42)(43)(44)(45). Pharmacologic inhibition of either YAP or GLS1 also effectively improved rodent PAH.…”
Section: R E V I E W S E R I E S : M I T O C H O N D R I a L D Y S Fmentioning
confidence: 99%